2020
DOI: 10.24996/ijs.2020.61.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical Analysis of Well Logs for Asmari Reservoir in Abu Ghirab Oil Field, South Eastern Iraq

Abstract: The present study includes the evaluation of petrophysical properties and lithological examination in two wells of Asmari Formation in Abu Ghirab oil field (AG-32 and AG-36), Missan governorate, southeastern Iraq. The petrophysical assessment was performed utilizing well logs information to characterize Asmari Formation. The well logs available, such as sonic, density, neutron, gamma ray, SP, and resistivity logs, were converted into computerized data using Neuralog programming. Using Interactive petrophysics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Upper Kirkuk Reservoir is a middle reservoir of Asmari formation, deposited during [15]. [21] on his study showed C zone as a part of Upper Kirkuk reservoir with title Buzurgan member, this difference of characterization due to evaluation diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Upper Kirkuk Reservoir is a middle reservoir of Asmari formation, deposited during [15]. [21] on his study showed C zone as a part of Upper Kirkuk reservoir with title Buzurgan member, this difference of characterization due to evaluation diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars and oil firms are interested in the Zagros Fold Belt. (Amel et al, 2021;Fouad, 2012;Al-Baldawi, 2020;Al-Saad and Al-Shahwan, 2019;Al-Baldawi, 2015).…”
Section: Introductionmentioning
confidence: 99%